Trans-Atlantic Passages - Mitchell, J. author. aut Link
XIV, 299 p.
Keywords: Philip Hale (1854-1934) helped put Boston on the Transatlantic map through his music writing. Mitchell reconstructs Hale's oeuvre to produce an authoritative account of the role the Boston Symphony played in the international world of nineteenth- and early twentieth-century music.